2016
DOI: 10.1016/j.enggeo.2015.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Application of microbially induced calcite precipitation in erosion mitigation and stabilisation of sandy soil foreshore slopes: A preliminary investigation

Abstract: Eroding foreshores endanger the floodplains of many estuaries, as such, effective and environmentally friendly interventions are sought to stabilise slopes and mitigate erosion. As a step in forestalling these losses, we developed laboratory microcosms to simulate tidal cycles and examined the mechanisms of erosion and failure on sandy foreshore slopes. As an experimental aim, we applied microbially induced calcite precipitation (MICP) to selected slopes and compared the effectiveness of this microbial geo-tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(59 citation statements)
references
References 38 publications
0
59
0
Order By: Relevance
“…In a study to mitigate soil erosion [146], a maximum increase of 0.6 MPa in the UCS of a soil treated with MICP was obtained. Studies by Jijian [147] revealed an improvement in the UCS of a sand column of up to 1.91 MPa after employing a biogrouting method which effectively hardened black sands.…”
Section: Shear Strength Characteristicsmentioning
confidence: 99%
“…In a study to mitigate soil erosion [146], a maximum increase of 0.6 MPa in the UCS of a soil treated with MICP was obtained. Studies by Jijian [147] revealed an improvement in the UCS of a sand column of up to 1.91 MPa after employing a biogrouting method which effectively hardened black sands.…”
Section: Shear Strength Characteristicsmentioning
confidence: 99%
“…In another case, MICP was found to have the potential to simultaneously immobilize heavy metals in a brownfield soil as well as strengthening the soil for construction purposes (Jiang, Liu, Du, & Bi, 2019a). Other multi-functional applications of MICP including shoreline protection (Salifu, MacLachlan, Iyer, Knapp, & Tarantino, 2016), geological hazard mitigation (Jiang, Tang, Yin, Xie, & Shi, 2019b), soil and water conservation, and pollution control for radionuclides are also under active research, though mostly at a preliminary stage. Nevertheless, more research effort is needed to develop multifaceted MICP protocols that could address multidisciplinary engineering challenges by coupling soil engineering performance enhancement with ecological, environmental and carbon footprint benefits.…”
Section: Multi-functionalit Ymentioning
confidence: 99%
“…Therefore, sustainable and eco-friendly materials and systems are in demand for the protection against coastal erosion. Countermeasures against coastal erosion protection have been studied by many researchers [1], including hard and soft structures focusing on urea degradation bacteria. However, all these methods have an adverse effect on the surrounding landscape, environment, and ecosystem [2]; moreover, eco-sustainability is another major concern.…”
Section: Introductionmentioning
confidence: 99%